Application of porous metal enrichment probe sampling to single cell analysis using matrix‐assisted laser desorption ionization time of flight mass spectrometry (MALDI‐TOF‐MS). (1st December 2015) - Fu, Qiang; Tang, Jun; Cui, Meng; Xing, Junpeng; Liu, Zhiqiang; Liu, Shuying
Abstract : There is an increasing need for analyzing metabolism in a single cell, which is important to understand the nature of cellular heterogeneity, disease, growth and specialization, etc. However, single cell analysis is often challenging for the traces of samples. In the present study, porous metal enrichment probe sampling combined with matrix‐assisted laser desorption ionization time of flight mass spectrometry( MALDI‐TOF‐MS) has been applied for in situ analysis of live onion epidemic cell. Porous probe, treated by corroding copper wire with HCl, was directly inserted into a single cell to get cell solution. A self‐made linear actuator was enough to control the penetration of probe into the target cell accurately. Then samples on the tip of probe were eluted and detected by a commercial MALDI‐TOF‐MS directly. The formation of porous microstructure on the probe surface increased the adsorptive capacity of cell solution. The sensitivity of porous probe sampling was 6 times higher than uncorroded probes generally. This method provides a sensitive and convenient way for the sampling and detection of single cell solution. Copyright © 2015 John Wiley & Sons, Ltd.